Garbage Management using Internet of Things - Chaitra, D; Srinivas, Chetana (International Journal of Computer Sciences and Engineering, 2025)
The garbage bins placed at public or in a campus places are overflowing and it creates unhygienic conditions and also ugliness to that place. At the same time bad smell is spread with diseases. To avoid all such situations a project called Garbage collection bin overflow indicator using IOT (Internet of Things) technology can be implemented. Resultantly, smart cities with smart waste management systems can be implemented. One of the applications of IoT is the effectivein management of garbage for healthy environment for life on this green planet with greater efficiency. The purpose is to develop an IoT based costeffective system that can monitor the everyday garbage in real time by using smart technology with the help of android and web applicationand Ultrasonic sensors.